WEIRD Is Not Enough: Sustainability Insights from Non-WEIRD Countries - Wooliscroft, Ben; Ko, Eunju (SAGE Publications, 2023)
Henrich, Heine, and Norezayan (2010) published ‘The weirdest people in the world?’ in Behavoral and Brain Sciences (as of March, 2023 it has been cited 11 800 plus times in scholar.google). The paper introduced the concept of Western, Educated, Industrialised, Rich and Developed (WEIRD) countries/cultures and research subjects. It makes a cogent case for research based on those samples being unrepresentative of, and not useful to inform policy/behavior change/etc. of non-WEIRD countries. With this paper Henrich, Heine, and Norezayan (2010) have asked psychology and all social sciences to reflect on whether our findings represent the world, or just one small part of it. Macromarketing's assumptions and beliefs about fundamental human behavior have been shaped by psychology.
Keywords: 35 Commerce, Management, Tourism and Services; 3506 Marketing; Behavioral and Social Science; 1399 Other Education; 1505 Marketing; 2103 Historical Studies; Marketing; 3506 Marketing